2014
DOI: 10.1162/adev_a_00033
|View full text |Cite
|
Sign up to set email alerts
|

Afghanistan: Balancing Social and Security Spending in the Context of a Shrinking Resource Envelope

Abstract: For Afghanistan, the dual prospect of declining donor support and high ongoing security spending over the medium term keeps its government budget tight. This paper uses a general equilibrium model to capture the security–development trade-off facing the government in its effort to rehabilitate growth and fiscal sustainability. In particular, it considers strategic policy options for counteracting and minimizing the negative macroeconomic impact of possible aid and revenue shortfalls. We find that the mobilizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…This study assessed the degree of administrative capacity, labor investment, labor productivity, capital investment, efficiency of capital, terroristic activities, and issues of religion in relation to the developing process of the Aynak Copper Mine project in Afghanistan. In line with previous research on economic collaboration [2,[22][23][24] and Afghanistan [1, [25][26][27][28], the major finding of this current research is that the progressive process of developing the Aynak Copper Mine project is strongly associated with the factors of DAC, TAs, and RIs. One of the most significant results showed that a lack of strong administrative capacity may be an obstacle in developing the Aynak Copper Mine.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study assessed the degree of administrative capacity, labor investment, labor productivity, capital investment, efficiency of capital, terroristic activities, and issues of religion in relation to the developing process of the Aynak Copper Mine project in Afghanistan. In line with previous research on economic collaboration [2,[22][23][24] and Afghanistan [1, [25][26][27][28], the major finding of this current research is that the progressive process of developing the Aynak Copper Mine project is strongly associated with the factors of DAC, TAs, and RIs. One of the most significant results showed that a lack of strong administrative capacity may be an obstacle in developing the Aynak Copper Mine.…”
Section: Discussionsupporting
confidence: 86%
“…As Table 1 shown, we collected data from the six groups of stakeholders and then we placed them into five categories: None or few (0-20), not too much (21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37)(38)(39)(40), neutral (41-60), partial (61-80), and very much (81-100). Among the 2563 responses related to the DAC, 62 people (2.4%) realized that the Afghan Government has no or few DACs to influence the development process of the Aynak Copper Mine, and 524 (20.4%) considered that there is not too much the DAC of the Afghan Government can do with the development of the Aynak Copper Mine.…”
Section: Variable Definitionsmentioning
confidence: 99%